1999
DOI: 10.1038/15525
|View full text |Cite
|
Sign up to set email alerts
|

A humanized model for multiple sclerosis using HLA-DR2 and a human T-cell receptor

Abstract: Multiple sclerosis (MS) is a complex chronic neurologic disease with a suspected autoimmune pathogenesis. Although there is evidence that the development of MS is determined by both environmental influences and genes, these factors are largely undefined, except for major histocompatibility (MHC) genes. Linkage analyses and association studies have shown that susceptibility to MS is associated with genes in the human histocompatibility leukocyte antigens (HLA) class II region, but the contribution of these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
219
3
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(230 citation statements)
references
References 30 publications
(21 reference statements)
5
219
3
3
Order By: Relevance
“…These experiments of course also require that the restricting human HLA molecule is also expressed transgenically in the model (see below). One group have described induction of an EAE-like disease in hu-TCR transgenic mice expressing a TCR directed against an immunodominant epitope of MBP [17]. We have also generated hu-TCR transgenic mice and find spontaneous autoimmunity associated with an overtly Th1 response to MBP peptide (manuscript in preparation).…”
Section: Transgenic Mice Expressing T Cell Receptors Derived From Autmentioning
confidence: 98%
“…These experiments of course also require that the restricting human HLA molecule is also expressed transgenically in the model (see below). One group have described induction of an EAE-like disease in hu-TCR transgenic mice expressing a TCR directed against an immunodominant epitope of MBP [17]. We have also generated hu-TCR transgenic mice and find spontaneous autoimmunity associated with an overtly Th1 response to MBP peptide (manuscript in preparation).…”
Section: Transgenic Mice Expressing T Cell Receptors Derived From Autmentioning
confidence: 98%
“…It would be challenging to address the efficacy in preventing antigen-induced EAE development using different native proteins and engineered peptides fragments as well as showing efficacy in genetically modified animals exhibiting spontaneous EAE [11,12]. Also, it would be interesting to see the effects in animal models of other autoimmune diseases, such as rheumatoid arthritis, diabetes and psoriasis.…”
Section: Target Validation and Drug-development Perspectivesmentioning
confidence: 99%
“…Some functional differences were reported when comparing T cell responses to myelin antigens in MS as compared to controls. For example, differences were reported with respect to cytotoxic properties [7]. Probably the best evidence for a direct pathogenic role of MBP reactive T cells comes from a clinical trial where it was demonstrated that MS patients treated with an altered peptide ligand based on the MBP(83-99) epitope developed clinical worsening, increased brain inflammation and increased anti-MBP T cell responses [8].…”
Section: Myelin Reactive T Cells: Key Players In Msmentioning
confidence: 99%